New developments in international commercial and consumer law : proceedings of the 8th Biennial Conference of the International Academy of Commercial and Consumer Law /: proceedings of the 8th Biennial Conference of the International Academy of Commercial and Consumer Law. (1998) - Unknown
No abstract available